1999
DOI: 10.1038/11320
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virus therapy of multiple tumors in the brain requires suppression of innate and elicited antiviral responses

Abstract: The occurrence of multiple tumors in an organ heralds a rapidly fatal course. Although intravascular administration may deliver oncolytic viruses/vectors to each of these tumors, its efficiency is impeded by an antiviral activity present in complement-depleted plasma of rodents and humans. Here, this activity was shown to interact with complement in a calcium-dependent fashion, and antibody neutralization studies indicated preimmune IgM has a contributing role. Short-term exposure to cyclophosphamide (CPA) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
277
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(285 citation statements)
references
References 32 publications
(35 reference statements)
5
277
2
1
Order By: Relevance
“…It has been demonstrated that plasma inactivates viral particles via complement and non-complement pathways of action. 31 Plasma modified, noninfectious particles may have a significantly different distribution from infectious particles, pointing to the need for verification studies using histochemistry for the identification of virion components, active infection and marker gene expression studies. Studies to distinguish infectious from noninfectious particles may also become feasible with greater understanding of the molecular biology of viral binding and entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that plasma inactivates viral particles via complement and non-complement pathways of action. 31 Plasma modified, noninfectious particles may have a significantly different distribution from infectious particles, pointing to the need for verification studies using histochemistry for the identification of virion components, active infection and marker gene expression studies. Studies to distinguish infectious from noninfectious particles may also become feasible with greater understanding of the molecular biology of viral binding and entry into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-arterial administration may benefit from tempering of the innate anti-viral activity of plasma by immune suppression. 31 Alternatively, circulating antibodies could be saturated by the administration of viral glycoproteins before viral vector injection. Delivery vehicles, such as gels or migratory cells could be utilized to gradually release virus into the tumor bed or beyond.…”
Section: Discussionmentioning
confidence: 99%
“…44 Cyclophosphamide, which depresses innate IgM levels and complement activation in rats, as well as other immune functions, also enhanced viral transduction of intracerebral tumors after intracarotid delivery with BBBD and extended the survival of U87dEGFR glioma-bearing nude rats. 45 We have not examined the impact of complement activation in our model, which might have resulted in even greater efficacy, although the complement pathway in mice is somewhat different from rats. 44,46,47 After gaining access to the brain parenchyma, the ability of G47D to replicate specifically in tumor cells and spread throughout the tumor is apparent from continued labeling of the tumor for at least 19 days after injection.…”
Section: Oncolytic Hsv Therapy Of Brain Tumors After Bbbd R Liu Et Almentioning
confidence: 99%
“…Un autre composé d'intérêt, la cyclophosphamide, présente une action provirale en plus de ses propriétés cytotoxiques directes. En effet, elle peut réduire la réponse immunitaire antivirale, entre autres par l'inhibition de la synthèse d'anticorps neutralisants [36]. Plus récemment, des stratégies de criblage ont révélé de nouveaux candidats capables d'améliorer l'activité des virus oncolytiques.…”
Section: Stratégies Pharmacovirales : Virus Oncolytiques Combinés à Dunclassified